Astrotourism as strategic alternative of territorial development: the case of the Estrella Region of Chile - Araya-Pizarro, Sebastián (2020)
The privileged conditions of the skies of northern Chile have allowed the Coquimbo Region to position itself as the world capital of astronomy and forges a unique local identity: that of the Star Region. However, these advantages have not managed to consolidate a systemic competitive offer that allows taking advantage of the patrimonial wealth that the territory offers. On July 2, 2019, the country experienced one of the most important astronomical events in the world: The Total Solar Eclipse, a phenomenon that involved the arrival of more than 300 thousand passengers and provided the opportunity to explore the complacency of the visitor with their stay. In this context, the objective of this study was to analyze the profile and satisfaction of the foreign tourist who participated in the mega-event. The data was collected through a survey applied to 228 tourists, and was then analyzed using a binary logistic regression. The results revealed the existence of various attributes of the visitor's profile and tourist aspects that influence their level of satisfaction (sex, use of e-commerce, astronomical offer, accommodation, signage, cleaning, financial resources, entertainment and tourist information). It concludes on the need to strategically plan the destination under a synergic holistic approach, which considers both the contextual tourist aspects of the area and the differentiating attributes of the value proposition offered to passengers. In this way, the potential of astronomical tourism could be exploited as a strategic alternative for territorial revitalization.